PREPARATION, CHARACTERIZATION, AND IN VITRO ANTI CANCER ACTIVITY EVALUATION OF IRINOTECAN AND SUNITINIB-LOADED NANOBUBBLES - PATAMSETTI, ANJANEYULU; GUBBIYAPPA, KUMAR SHIVA (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of the present research is to develop, analyze, and evaluate the cytotoxic effects of nanobubbles loaded with irinotecan and sunitinib for colorectal cancer therapy. Methods: Drug-loaded dextran sulfate nanobubbles were formulated using the emulsification technique and the prepared nanobubbles were evaluated for qualitative and quantitative parameters. Cell viability MTT assay was performed to evaluate the irinotecan and sunitinib-loaded nanobubbles for cytotoxicity or ability to inhibit cell proliferation spectrophotometrically as a function of mitochondrial activity in living CR4 and A-549(irinotecan), CR4 and A-498 (sunitinib) cell lines. Results: The irinotecan and sunitinib-loaded nanobubbles were successfully prepared, with all qualitative and quantitative parameters within the acceptable range. The optimized nanobubbles demonstrated excellent physicochemical properties, with particle sizes of 177.8±5.2 nm for sunitinib and 89.8±9.5 nm for irinotecan. In vitro drug release studies showed significantly enhanced release profiles, with ultrasound-triggered drug release reaching 99% for both drugs, compared to only 39% for plain sunitinib and 35% for plain irinotecan. This highlights the ability of nanobubbles to enable controlled and targeted drug delivery, potentially improving therapeutic precision. The in vitro anticancer activity results revealed IC50 values of 70.41 and 73.26 µg/ml for irinotecan against CR4 and A-549 cell lines, respectively, and 84.34 and 60.08 µg/ml for sunitinib against CR4 and A-498 cell lines, respectively, demonstrating strong cytotoxic effects. Conclusion: The nanobubble-based delivery system enhances drug bioavailability, cellular uptake, and tumor penetration, thereby improving cytotoxic efficacy compared to conventional drug formulations. These findings underscore the potential of ultrasound-responsive nanobubbles as a promising strategy for targeted colorectal cancer therapy, potentially leading to improved treatment outcomes with reduced systemic toxicity.